2001
DOI: 10.1016/s0928-8244(01)00264-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and killing of Listeria monocytogenes by normal human peripheral blood granulocytes and monocytes as measured by flow cytometry and cell sorting

Abstract: Cellular components of innate immunity (NK cells, monocytes and granulocytes) play an important role in early resistance to Listeria monocytogenes in the mouse model. Minimally invasive methods of measuring the bacteriocidal capacity of these cells may be useful as a biomarker of susceptibility in humans. A technique was developed whereby the uptake and survival of L. monocytogenes could be measured in human granulocytes and monocytes using small volumes of peripheral blood. This method used flow cytometry to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is in agreement with Raybourne et al who suggested that human blood monocytes could not support the growth of L. monocytogenes over time (48). It is possible that activity of the pore-forming toxin LLO is impaired in monocytes.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with Raybourne et al who suggested that human blood monocytes could not support the growth of L. monocytogenes over time (48). It is possible that activity of the pore-forming toxin LLO is impaired in monocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Killing of bacteria was measured as described previously [25,27]. Briefly, overnight cultures of L. monocytogenes (1ϫ10 7 cells/ml) and S. aureus (1ϫ10 7 cells/ml) were opsonized by incubation with 0.1% gelatin (w/v) and 10% (v/v) human AB serum in HBSS, where 1 ml containing 1 ϫ 10 7 opsonized bacteria was added to 1 ϫ 10 7 cells/ml in 100 l HBSS and incubated at 37°C for 3 min with continuous rotation to promote phagocytosis.…”
Section: Bactericidal Activitymentioning
confidence: 99%
“…Using microscopy, the number and the distribution or location of bacteria within host cells or cell-associated bacteria can be determined in a quantitative manner as, for example, shown by Malik-Kale et al [ 30 ] who made use of mCherry expressing Salmonella . By measuring mean fluorescence intensities, flow cytometry enables semi-quantitative analyses as demonstrated by Raybourne et al [ 31 ] who compared the intracellular L. monocytogenes content of human monocytes and granulocytes by pre-labeling bacteria with a lipophilic fluorescent dye. Isolation of infected cells using fluorescence-activated cell sorting (FACS) typically relies on the exogenous expression of fluorescent proteins, like green fluorescent protein (GFP), by pathogens [ 32 , 33 , 34 , 35 ].…”
Section: Current Limitations For the Application Of Omics In Host–mentioning
confidence: 99%